An expert stakeholder's view on European integration challenges - Amelie F. Constant; Martin Kahanec; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2010)
The standard approach of analyzing gaps in social and labor market outcomes of different ethnic groups relies on analysis of statistical data about the affected groups. In this paper we go beyond this approach by measuring the views of expert stakeholders involved in minority integration. This enables us to better understand the risk of minority exclusion; the inner nature of discrimination, negative attitudes and internal barriers; as well as the ethnic minorities' desires and perceptions about which approaches are better than others in dealing with integration challenges. Main findings are that ethnic minorities do want to change their situation, especially in terms of employment, education, housing and attitudes towards them. Insufficient knowledge of the official language, insufficient education, discriminatory attitudes and behavior towards ethnic minorities as well as institutional barriers, such as citizenship or legal restrictions, seem to constitute the key barriers to their social and labor market integration.
Keywords: J15; J71; J78; 330; attitudes; opinions; immigrants; ethnic minorities; labor market